The Rise of Brand Patanjali: A Review of the Efficacy of the Patanjali Brand in the Indian Fast Moving Consumer Goods Market Compared to Other Global Brands (International Journal of Innovative Research in Engineering & Management, 2021)
Because of its massive population, India is a big market for  Fast-Moving Consumer Goods (FMCG) firms. There are  currently a number of large and minor companies on the market  with substantial clout. The purpose of this article is to examine  why the Patanjali brand has grown so quickly in the market. It  is apparent that Patanjali's path has not been simple, since  Patanjali is a relatively young company. However, Patanjali's  positioning, branding, and eventual strategy to build consumer  confidence and trust made a difference, and Patanjali's market  share grew so quickly that it overtook numerous items from  well-known brands in only 2 to 3 years, propelling it to the top  of the market. Ramdev's marketing approach was executed  flawlessly in the market, and his key formula was "swadeshi,"  which worked wonders in attracting a large number of  consumers as well as a huge proportion of raw material  suppliers, i.e. Indian farmers. It is still necessary to promote  locally grown and made goods.
Keywords: Customer; Consumer; Foods; Patanjali; Swadeshi